Combination of dynamic 11C-PIB PET and structural MRI improves diagnosis of Alzheimer's disease. Issue 2 (30th August 2015) - Liu, Linwen; Fu, Liping; Zhang, Xi; Zhang, Jinming; Zhang, Xiaojun; Xu, Baixuan; Tian, Jiahe; Fan, Yong
Abstract: Structural magnetic resonance imaging (sMRI) is an established technique for measuring brain atrophy, and dynamic positron emission tomography with 11 C-Pittsburgh compound B ( 11 C-PIB PET) has the potential to provide both perfusion and amyloid deposition information. It remains unclear, however, how to better combine perfusion, amyloid deposition and morphological information extracted from dynamic 11 C-PIB PET and sMRI with the goal of improving the diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI). We adopted a linear sparse support vector machine to build classifiers for distinguishing AD and MCI subjects from cognitively normal (CN) subjects based on different combinations of regional measures extracted from imaging data, including perfusion and amyloid deposition information extracted from early and late frames of 11 C-PIB separately, and gray matter volumetric information extracted from sMRI data. The experimental results demonstrated that the classifier built upon the combination of imaging measures extracted from early and late frames of 11 C-PIB as well as sMRI achieved the highest classification accuracy in both classification studies of AD (100%) and MCI (85%), indicating that multimodality information could aid in the diagnosis of AD and MCI. Highlights: Dynamic 11 C-PIB PET provides both perfusion and amyloid deposition information. Dynamic 11 C-PIB PET and MRI provide complementary information for diagnosis of AD. Multimodality information is helpful in classification studies with outlier samples.